ANALYSIS OF KNOWLEDGE FACTORS AND ACTIVITY PATTERNS ON STUNTING IN ADOLESCENTS (JUNIOR HIGH SCHOOL) THROUGH NUTRITIONAL PATTERNS IN BINTAN REGENCY IN 2024 - Suharti, Suharti; Artia Diarina; Alkausyari Aziz; Elsa Gusrianti (Bajang Institute, 2024)
Prevention and control of stunting require holistic and integrated efforts. Efforts to improve nutrition are activities carried out in an integrated, integrated, and sustainable manner to improve and maintain nutritional status in the community. Reducing stunting cases requires collaboration between health and non-health sectors in the form of promotive, preventive, curative, and rehabilitative efforts carried out by the local government and the community. The purpose of this study was to analyze knowledge factors and activity patterns on stunting in adolescents through nutritional patterns in Bintan Regency. The method in this study uses a quantitative method with analytical descriptions. The population in this study were residents in Bintan Regency. The sample of this study was 40 respondents which will be carried out in April-December 2023. The research instrument used a questionnaire on the material The Influence of Knowledge Factors and Activity Patterns on Stunting in Adolescents Through Nutritional Patterns. The results of the study showed that for knowledge about stunting, most students had sufficient knowledge (200 respondents (64%), for activity patterns towards nutrition at positive risk (225 respondents (70%) and analysis of the relationship between knowledge and activity patterns towards stunting in adolescents (junior high school) through nutritional patterns did not show a significant relationship because (p <0.05).